Assessment of neutrophil subsets and immune checkpoint inhibitor expressions on T lymphocytes in liver transplantation: A preliminary study beyond the neutrophil-lymphocyte ratio - Riff, Arnaud; Haem Rahimi, Muzhda; Delignette, Marie-Charlotte; Gossez, Morgane; Coudereau, Rémy; Pantel, Solène; Antonini, Teresa; Villeret, François; Zoulim, Fabien; Mabrut, Jean-Yves; Dumortier, Jérome; Venet, Fabienne; et al. (Frontiers in Physiology, 2023)
Advanced stages of cirrhosis are characterized by progressive immune alterations known as CAID (Cirrhosis Associated Immune Dysfunction). In advanced cirrhosis, liver transplantation (LT) remains the only curative treatment. Sepsis, shares many similarities with decompensated cirrhosis in terms of immuno-inflammatory response. In both conditions, the neutrophil-lymphocyte ratio (NLR) is associated with poor outcomes. Based on alterations in sepsis, we hypothesized that we could observe in cirrhotic and LT patients more detailed neutrophil and lymphocyte phenotypes. To this end, along with leukocyte count, we assessed immature neutrophils, LOX-1+MDSC and PD-1 and TIM-3 lymphocyte expressions in cirrhotic patients before transplantation in association with liver disease severity and during the first month after transplantation. We conducted a prospective monocentric study including cirrhotic patients registered on LT waiting-list. Blood samples were collected at enrolment before LT and for one month post-LT. In addition to NLR, we assessed by whole blood flow cytometry the absolute count of immature neutrophils and LOX-1+MDSC as well as the expressions of immune checkpoint receptors PD-1 and TIM-3 on T lymphocytes. We included 15 healthy volunteers (HV) and 28 patients. LT was performed for 13 patients. Pre-LT patients presented with higher NLR compared to HV and NLR was associated with cirrhosis severity. Increased immature neutrophils and LOX-1+MDSC counts were observed in the most severe patients. These alterations were mainly associated with acute decompensation of cirrhosis. PD-1 and TIM-3 expressions on T lymphocytes were not different between patients and HV. Post-LT immune alterations were dominated by a transitory but tremendous increase of NLR and immature neutrophils during the first days post-LT. Then, immune checkpoints and LOX-1+MDSC tended to be overexpressed by the second week after surgery. The present study showed that NLR, immature neutrophils and LOX-1+MDSC counts along with T lymphocyte count and checkpoint inhibitor expression were altered in cirrhotic patients before and after LT. These data illustrate the potential interest of immune monitoring of cirrhotic patients in the context of LT in order to better define risk of sepsis. For this purpose, larger cohorts of patients are now necessary in order to move forward a more personalised care of LT patients.